Preparation and characterization of a novel intelligent starch/gelatin binary film containing purple sweet potato anthocyanins for Flammulina velutipes mushroom freshness monitoring. (30th March 2023) - Zong, Zihao; Liu, Meng; Chen, Hangjun; Farag, Mohamed A.; Wu, Weijie; Fang, Xiangjun; Niu, Ben; Gao, Haiyan
Graphical abstract: Highlights: Novel Intelligent starch/gelatin films containing purple sweet potato anthocyanins were prepared. Compared with starch film, the mechanical properties of film were enhanced by adding gelatin. SG11 film can be developed as a visible intelligent label to monitor the freshness of F. velutipes. Abstract: In this study, intelligent food package was developed and characterized by loading purple sweet potato polyphenolic extract (SPS) into starch/gelatin film. The application of this film in indicating the freshness of Flammulina velutipes was also determined. The color of SPS buffer changed from red to blue and final yellow when pH increasing from 3 to 10. The blending film with starch/gelatin ratio of 1:1 wt showed a minimum water vapor permeability of 6.26 × 10 −11 gs −1 m −1 Pa −1 . The value of elongation at break and tensile strength of the starch/gelatin film with starch/gelatin ratio of 1:1 wt increased to 78.89 % and 11.70 MPa. Upon its application to monitor of F. velutipes freshness level, SG11 film color changed from initially green to purplish gray and finally to yellow as F. velutipes deteriorated post storage. Our results suggested that SG11 films could be used as an intelligent packaging material in the future for other food products.